A new combination in Myrcia (Myrtaceae) from Brazil - Maruyama, Adriano Da Silva De Cicco; Gaem, Paulo Henrique; Mazine, Fiorella Fernanda (Phytotaxa, 2024)
Myrcia De Candolle (1827: 406) is the second most species-rich genus of Myrtaceae in the Neotropics, with ca. 800 species (POWO 2023). About half of these species occur in Brazil (Santos et al. 2023). During the taxonomic study of Myrtaceae collections in São Paulo, it became evident that nomenclatural and taxonomic adjustments were necessary for one species of Myrcia, which we propose in the present work. Images of materials available online are cited by reference to herbarium acronyms (following Thiers 2023) and were consulted online via CRIA (2023) and JSTOR (2023).